2019
DOI: 10.1002/stc.2322
|View full text |Cite
|
Sign up to set email alerts
|

Curvelet transform-based identification of void diseases in ballastless track by ground-penetrating radar

Abstract: Summary Void disease caused by construction quality and external loads contributes to the failure of reinforced concrete (RC) structures. Ground‐penetrating radars have been used for various applications to detect void diseases beneath RC. However, interferences, such as strong reinforcement bar (rebar) reflection and multiple waves, complicate the identification of internal void diseases in RC. On the basis of these problems, we consider the ballastless track of high‐speed railways as a research object and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…We also found that the system would be less chaotic with the smaller order and larger coefficient of the fractional-order derivative. e fractional-order derivative was introduced to more accurately describe the nonlinear dynamic behaviors of physical objects with fractional-order characteristics, such as viscoelastic materials, damping, dynamic characteristics of gear clearance, friction, and impact in mechanical systems [45][46][47][48].…”
Section: Effect Of System Parameters On the Chaoticmentioning
confidence: 99%
“…We also found that the system would be less chaotic with the smaller order and larger coefficient of the fractional-order derivative. e fractional-order derivative was introduced to more accurately describe the nonlinear dynamic behaviors of physical objects with fractional-order characteristics, such as viscoelastic materials, damping, dynamic characteristics of gear clearance, friction, and impact in mechanical systems [45][46][47][48].…”
Section: Effect Of System Parameters On the Chaoticmentioning
confidence: 99%
“…Therefore, the real-time monitoring of track slab performance and the identification of the damage condition of track slabs are essential for long-term safe operation of the HSR. Existing track slab defect detection methods can be divided into three categories: visual inspection [15,16], nondestructive testing (NDT) [4,11,[17][18][19][20][21][22], and structural health monitoring (SHM) [23][24][25][26][27]. Most of the visual inspection methods rely on a variety of track inspection equipment, such as road rulers, gauges, and various customized equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Abdel et al applied four edge detectors for finding the concrete cracks, and a fast Haar transform was identified as the best solution [2]. In [3], curvelet transform is utilized for detecting the void diseases in ballast-less track, which may result in the cracks of the track slab. Hutchinson developed one Canny edge-based crack detection, which utilized a semi-automatic threshold value [4].…”
Section: Introductionmentioning
confidence: 99%
“…(2) Crack region identification should have a low computing burden and can be quickly updated incrementally. (3) Considering that there may be some background disturbances (e.g., handwriting, etc.) similar to cracks, how to minimize the relevance between cracks and those noises is an important quality of robust crack detection.…”
Section: Introductionmentioning
confidence: 99%